The effect of cortical repetitive transcranial magnetic stimulation on cognitive event-related potentials recorded in the subthalamic nucleus - Baláz, M; Srovnalová, H; Rektorová, I; Rektor, I (Experimental brain research, 2010)
We studied whether the cognitive event-related potentials (ERP) in the subthalamic nucleus (STN) are modified by the modulation of the inferior frontal cortex (IFC) and the dorsolateral prefrontal cortex (DLPFC) with repetitive transcranial magnetic stimulation (rTMS). Eighteen patients with Parkinson's disease who had been implanted with a deep brain stimulation (DBS) electrode were included in the study. The ERPs were recorded from the DBS electrode before and after the rTMS (1 Hz, 600 pulses) over either the right IFC (10 patients) or the right DLPFC (8 patients). The ERPs were generated by auditory stimuli. rTMS over the right IFC led to a shortening of ERP latencies from 277 +/- 14 ms (SD) to 252 +/- 19 ms in the standard protocol and from 296 +/- 17 ms to 270 +/- 20 ms in the protocol modified by a higher load of executive functions (both P < 0.01). The application of rTMS over the DLPFC and the sham stimulation over the IFC showed no significant changes. The shortening of ERP latency after rTMS over the right IFC reflected the increase in the speed of the cognitive process. The rTMS modulation of activity of the DLPFC did not influence the ERP. Connections (the IFC-STN hyperdirect pathway) with the cortex that bypass the BG-thalamocortical circuitries could explain the position of the STN in the processing of executive functions.
Keywords: reakční čas; mapování mozku; Analysis of Variance; Electroencephalography; Male; Psychomotor Performance; Auditory Perception; transkraniální magnetická stimulace; Transcranial Magnetic Stimulation; psychomotorický výkon; čelní lalok; Evoked Potentials; Subthalamic Nucleus; elektroencefalografie; Executive Function; Reaction Time; exekutivní funkce; mužské pohlaví; Neural Pathways; implantované elektrody; akustická stimulace; počítačové zpracování signálu; evokované potenciály; Frontal Lobe; Electrodes, Implanted; Brain Mapping; sluchová percepce; lidé; ženské pohlaví; analýza rozptylu; Humans; Acoustic Stimulation; nervové dráhy; nucleus subthalamicus; Signal Processing, Computer-Assisted; Female; Parkinson Disease; Parkinsonova nemoc; lidé středního věku; Middle Aged